Effect of aqueous extract of leaves Origanun vulgare on some metabolites and hormonal composition in blood of adolescent rabbits - Abeed, Marwa N.; AL-Najar, Aftekar M. (Journal of Kerbala for Agricultural Sciences, 2018)
The study was conducted in animal field and laboratories which belonged to Department of Animal Production Technique, Technical College – Al-Musiab from September 2015 to January 2016 to study the effect of effect of aqueous extract of Origanun vulgare (OV) leaves on some metabolites and hormonal in blood of adolescent rabbits, breeding deBouscat white (France) aged 12 weeks with an average weight 2.5-3 kg were randomly divided into 4 equal groups, 9 rabbits for each in 3 replicates, each replicate contain 2 female and one male. Group A expressed as (control) received normal saline only, Group B receiving an aqueous extract of (OV) in concentration of 1 gm/kg/ Body weight (B.w), Group C receiving an aqueous extract of (OV) in concentration of 2 gm/kg/ B.w , Group C receiving an aqueous extract of (OV) in concentration of 3 gm/kg/ B.w. , orally for 7 days. The blood samples were collected after sacrificed of rabbits. The blood serum samples were analyzed to evaluate the metabolites and hormonal composition by using commercially available kits. The results showed that the total protein concentration was significantly increased (P<0.05), while the concentrations of total cholesterol, glucose and cratinine were non-significant. The result of measured of female hormones showed that the concentrations of Lutinizing hormone (LH), Follicle stimulating hormone (FSH), Prolactin hormone and insulin hormone were significantly increased (P<0.05), while the concentration of Estradiol hormone (E2) was highly significantly increased (P<0.01). The results of measured of male hormones showed that the concentration of insulin hormone was highly significantly increased (P<0.01), and significantly increased (P<0.05) in concentrations of LH and testosterone hormones. In conclusions from this study that the aqueous extract of (OV) leaves are regulate of sexual hormones , ovarian functions and increasing fertility in rabbits.